Video Materials in Speech Practice Classes for Students Majoring in English as Their Second Foreign Language - Турченко, Віра Олександрівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article is dedicated to the studying peculiarities of using video materials at English lessons. Video materials are considered to Ье an effective means of communicative skills formation, promote students’ motivation development for language studying. The stages ofwork with video materials are regarded as well as the exercise system for the students’ implementation is developed and described in the research paper.